The Policy Drivers of Self-Employment: New Evidence from Europe - Annabelle Mourougane; Balázs Égert; Mark Baker; Gábor Fülöp (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using cross-country time series panel regressions for the last two decades, this paper seeks to identify the main policy and institutional factors that explain the share of self-employment across European countries. It looks at the aggregate share of self-employed as well as its breakdown by age, skill and gender. The generosity of unemployment benefits, and to a lesser extent, spending on active labour market policies appear to be robust determinants of the long-term share of self-employed in European countries. No significant relation could be identified between the stringency of employment protection and aggregate self-employment. However, there are significant, and oppositely signed, impacts on high- and low-skilled self-employed separately. Both the tax wedge and the minimum wage appear to be related positively to the share of self-employed in the long term, but the relation holds for some categories of workers only.
Keywords: J01; J21; J41; J48; 330; self-employment; labour market; labour market regulations; labour market institutions; Europe